Neutrophil extracellular traps as a potential source of autoantigen in cocaine-associated autoimmunity - Lood, Christian; Hughes, Grant C (Rheumatology (Oxford, England), 2017)
Exposure to illicit cocaine and its frequent adulterant, levamisole, is associated with ANCAs targeting neutrophil elastase (NE), neutropenia and vasculitic/thrombotic skin purpura. The mechanisms of cocaine/levamisole-associated autoimmunity (CLAA) are unknown. The aim of this study was to assess the ability of cocaine and levamisole to induce the release of neutrophil extracellular traps (NETs), a potential source of autoantigen and tissue injury. We performed quantitative and qualitative assessment of NET formation in neutrophils from healthy donors exposed to either drug in vitro . In addition, IgG from sera of individuals with CLAA (CLAA-IgG) was assessed for its ability to enhance formation of, and to bind to, drug-induced NETs. Both cocaine and levamisole could induce formation of NETs enriched in NE and, potentially, inflammatory mitochondrial DNA. Both drugs could also augment simultaneous release of B cell-activating factor belonging to the TNF family (BAFF). CLAA-IgG, but not IgG from healthy individuals, could potentiate drug-induced NETosis. Furthermore, CLAA-IgG, but not ANCA + control IgG, bound to drug-induced NETs in a pattern consistent with NE targeting. Both cocaine and levamisole may contribute to the development of ANCAs by inducing release of potentially inflammatory NETs in association with NE autoantigen and BAFF. Enhancement of drug-induced NET release by CLAA-IgG provides a potential mechanism linking vasculitis/pupuric skin disease to acute drug exposure in patients with CLAA. Further study of this under-recognized form of autoimmunity will be likely to provide mechanistic insight into ANCA-associated vasculitis and other diseases associated with NETosis.